51st AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference<BR&amp;gt; 18th AIAA/ASME/AHS Adap 2010
DOI: 10.2514/6.2010-3025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clearance Fit and Friction Coefficient on Triple-Row Riveted Lap Joints

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Nonlinear material models for both the 2024-T3 aluminum alloy sheets and the 2117-T4 aluminum alloy universal head rivet are the same as ones used in Szolwinski and Farris 3 and Li et al 5,6 which were verified through the copious amounts of studies comparing experimental and numerical force-deflection response during the riveting process. The isotropic hardening behavior was assumed for the rivet and sheet materials with rate effects, which used power hardening rule, with the following equation…”
Section: Materials Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonlinear material models for both the 2024-T3 aluminum alloy sheets and the 2117-T4 aluminum alloy universal head rivet are the same as ones used in Szolwinski and Farris 3 and Li et al 5,6 which were verified through the copious amounts of studies comparing experimental and numerical force-deflection response during the riveting process. The isotropic hardening behavior was assumed for the rivet and sheet materials with rate effects, which used power hardening rule, with the following equation…”
Section: Materials Modelingmentioning
confidence: 99%
“…Residual stress induced by the expanding the rivet against the rivet hole's inner wall varies with several manufacturing parameters. Li et al 5,6 studied the effect of clearance between the rivet shank and the rivet hole, which is induced by manufacturing processes. Their results indicated that a small increase in the clearance considerably changed the driven rivet head dimensions.…”
Section: And Farris 3 Extendedmentioning
confidence: 99%
See 2 more Smart Citations
“…Szolwinski and Farris 3 analyzed a non-countersunk model and observed that greater squeeze force pushed the zone of tensile hoop stress away from the hole and also obtained an increased fatigue life. Li et al [4][5][6] and Rans et al 7,8 conducted numerical and experimental studies on the residual stress/strain after rivet installed and also had a further consideration of the stress variation under the tensile load and found that installation force played a significant role on fatigue behavior of riveted lap joints. Atre et al 9,10 and Cheraghi 11 utilized the finite element (FE) model to conduct parametric studies on the effects of varying hole clearance, misaligned holes, the presence of debris, skin defects, friction, applied rivet displacement, and sealant on the residual stress state in riveted lap joints.…”
Section: Introductionmentioning
confidence: 99%